2014
DOI: 10.1117/12.2037469
|View full text |Cite
|
Sign up to set email alerts
|

Graded-index core polymer optical waveguide for high-bandwidth-density optical printed circuit boards: fabrication and characterization

Abstract: We demonstrate that graded-index (GI) core polymer optical waveguides are a promising component realizing highbandwidth-density on-board interconnects. As a method for fabricating GI-circular-core polymer optical waveguides, we introduce the Mosquito method utilizing a microdispenser. The Mosquito method is capable of accurately controlling the core diameter and the inter-core pitch. We also demonstrate that the GI-core polymer waveguides enable remarkably low loss waveguide circuits involving waveguide crossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Greater control of the refractive index profiles can be achieved by altering other configurable parameters including choice of core and cladding materials, core monomer dispensing pressure and amending the scanning programme. It has been demonstrated that the graded index circular waveguides produced through this method outperform step index waveguides of similar size [6].…”
Section: Mosquito Fabrication Methods (Keio University)mentioning
confidence: 99%
“…Greater control of the refractive index profiles can be achieved by altering other configurable parameters including choice of core and cladding materials, core monomer dispensing pressure and amending the scanning programme. It has been demonstrated that the graded index circular waveguides produced through this method outperform step index waveguides of similar size [6].…”
Section: Mosquito Fabrication Methods (Keio University)mentioning
confidence: 99%
“…The dispensing scanning speed, inner needle diameter and dispensing pressure are key parameters in executing the Mosquito Method [16,19,22]. Hence, these three dispensing criteria are investigated to create the desired core diameter.…”
Section: Optimum Dispensing Conditionsmentioning
confidence: 99%
“…Thus, it is imperative to implement the graded index (GI) multimode fiber since the fiber is a promising candidate for high bitrate transmissions in which it has the advantage of low propagation loss, low connection loss with GI multimode fiber (MMF) with wide misalignment tolerance, and low interchannel crosstalk even under a small pitch size [15]. Correspondingly, the "Mosquito Method" is adopted to create the GI circular core [16][17][18][19] of the Eu-Al polymer optical waveguide. The circular core is important as this research attempts to combine optical fiber characteristics to a planar waveguide.…”
Section: Introductionmentioning
confidence: 99%